(untitled) (Yearbook - Faculty of Economics, 2013)
In this paper are investigated problems of poverty, economic growth, and income distribution. Than follows a simple econometric model, used to estimate correlation between infant mortality rates with income per capita in 50 US states in year 1990, including Washington DC in the analysis. Infant mortality rate is a proxy variable for poverty and is included as dependent variable in the analysis. Results from the estimation are in line with apriori knowledge. So it is Infant mortality rate variable is positively correlated with the population growth, and negatively correlated with the number of physicians per 100,000 civilian population, and income per capita.